2013
DOI: 10.1118/1.4788642
|View full text |Cite
|
Sign up to set email alerts
|

Toward simultaneous PET/MR breast imaging: Systematic evaluation and integration of a radiofrequency breast coil

Abstract: The successful integration of a four-channel RF breast coil with a defined table position together with the CT-based μ-maps provides a technical basis for future clinical PET/MR breast imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 20 publications
3
90
0
Order By: Relevance
“…These results demonstrate that disregarding the presence of MR coils leads to substantial regional bias in PET quantification and illustrate the importance of accurate implementation of methodology for MR coil attenuation correction (AC) in simultaneous PET/MR applications. Even though MR coils are invisible in the conventional MR-acquired AC maps, it was shown that coil AC can be successfully implemented using a CT-based template of the coil, which is fused with the MR-based AC-map of the patient [6,9,10]. …”
mentioning
confidence: 99%
“…These results demonstrate that disregarding the presence of MR coils leads to substantial regional bias in PET quantification and illustrate the importance of accurate implementation of methodology for MR coil attenuation correction (AC) in simultaneous PET/MR applications. Even though MR coils are invisible in the conventional MR-acquired AC maps, it was shown that coil AC can be successfully implemented using a CT-based template of the coil, which is fused with the MR-based AC-map of the patient [6,9,10]. …”
mentioning
confidence: 99%
“…For accurate quantification, attenuation maps of the coil elements in the FOV should be estimated and used during reconstruction. Because of a loss in counts, the global activity concentration will be underestimated when the coil is not accounted for in the attenuation correction (AC), but errors will be especially prevalent near the coil (33)(34)(35). The problem with the coils and other objects in the FOV, such as the bed, is that they provide no MR signal although they attenuate radiation.…”
Section: Mrmentioning
confidence: 99%
“…The problem with the coils and other objects in the FOV, such as the bed, is that they provide no MR signal although they attenuate radiation. Coils with a fixed position can easily be measured beforehand, for example, with CT, and used as a template in the AC (34,36). In a similar manner, the bed can be included in the AC.…”
Section: Mrmentioning
confidence: 99%
See 1 more Smart Citation
“…Using simulations, the authors demonstrated that this approach reduces the interframe registration error between activity and attenuation maps. The attenuation of fixed objects, such as patient bed, body, and rigid coils (i.e., head/neck, spine, and torso) can be measured using transmission sources ( 68 Ge or 137 Cs) 119 or CT scans 120 and incorporated into attenuation maps as templates. The patient table and coil templates generated from transmission scans are more accurate than those generated from CT scans owing to the lack of streaking artifacts caused by high-density metallic components.…”
Section: B5 Emission-based Attenuation/motion Estimationmentioning
confidence: 99%